Livestock CRP Vietnam 2019-2021 Site selection process - Douxchamps, Sabine; Teufel, Nils; Nguyen Thinh; Hung Nguyen-Viet; Poole, Elizabeth J. (International Center for Tropical Agriculture, 2019)
[The Livestock CRP can] focus on difficult regions with high poverty and ethnic minorities, showing how research can deliver impact in challenging area, but can also conduct active research in medium scale intensified livestock areas to address priority issues on market, feeds and forage, animal diseases, food safety, AMR and the environment. While poverty rates have reduced rapidly over the past decade at national level, there remain sizable pockets of poverty at regional level, particularly in North-West, Central Highlands and Mekong Delta regions. In these areas, livestock, particularly indigenous pigs and cattle, play an important livelihoods function and could raise household income if market access, productivity, and animal disease constraints are overcome. This suggests a need for a targeted, regional approach for livestockoriented research in Vietnam.